Suturing techniques with endoscopic clips and special devices after endoscopic resection. Issue 3 (3rd October 2022) - Nomura, Tatsuma; Sugimoto, Shinya; Temma, Taishi; Oyamada, Jun; Ito, Keichi; Kamei, Akira
Abstract : Endoscopic submucosal dissection is an established method for complete resection of large and early gastrointestinal tumors. However, methods to reduce bleeding, perforation, and other adverse events after endoscopic resection (ER) have not yet been defined. Mucosal defect closure is often performed endoscopically with a clip. Recently, reopenable clips and large‐teeth clips have also been developed. The over‐the‐scope clip enables complete defect closure by withdrawing the endoscope once and attaching the clip. Other methods involve attaching the clip‐line or a ring with an anchor to appose the edges of the mucosal defect, followed by the use of an additional clip for defect closure. Since clips are limited by their grasping force and size, other methods, such as endoloop closure, endoscopic ligation with O‐ring closure, and the reopenable clip over‐the‐line method, have been developed. In recent years, techniques often utilized for full‐thickness ER of submucosal tumors have been widely used in full‐thickness defect closure. Specialized devices and techniques for defect closure have also been developed, including the curved needle and line, stitches, and an endoscopic tack and suture device. These clips and suture devices are applied for defect closure in emergency endoscopy, accidental perforations, and acute and chronic fistulas. Although endoscopic defect closure with clips has a high success rate, endoscopists need to simplify and promote endoscopic closure techniques to prevent adverse events after ER.